if you're reading this it's too late: caution : read at you own risk! - Bosh, Pseudonymous; Pseudonymous Bosh (New York Hachette Book Group, 2008)
If You're Reading This, It's Too Late is the second book in The Secret Series by Pseudonymous Bosch, following Cass and Max-Ernest on a new mystery. As members of the Terces Society, they aim to find a magical artifact called the Sound Prism and protect a "homunculus" (a man-made man) from the evil Midnight Sun alchemists.
English